Taxonomic and Phylogenetic Assessment of the Euphorbiaceae: A Review - D. A. Patil2, H. A. Thakur1* and (Journal of Experimental Sciences, 2011)
The family Euphorbiaceae is assessed taxonomically and phylogenetically in the light of different disciplines of botany. It lacks anatomical homogenity, probable because of diverse habit and habitat. It is heterogenous palynologically, chemically and embryologically. It is, however, fairly homogenous from embryological point of view. The floral anatomical investigations indicate reduction in the number of floral whorls as well as the number of members of whorls from a supposedly 5 - merous, dichlamydeous, heterochlamydeous ancestral flower. A review of taxonomic features especially those from exomorphology, have always remained changing. The present review based on all-pervasive examination of exomorphology and endomorphology suggests close affinities of certain families of this alliance. However, few of them apparently closer because of unisexuality and reduced floral structure. Ã‚Â